(untitled) (American Journal of Social Development and Entrepreneurship, 2023)
This study investigated pre and post IFRS adoption on entrepreneurship entry and entrepreneurship exit from 2006-2017 using stacked data from annual financial statement of quoted companies. Data for the study were obtained from secondary sources and analysed using graphical and table presentation on Eview9 statistical package. Data for the work were drawn from samples of 72 observations Nigeria stock exchange statistical Bulletins. The descriptive statistics revealed high benefits of the Post instead of the Pre IFRS adoption which favours entrepreneurship entry and elimination entrepreneurship exist. Therefore, overall the relevance of reporting method using IFRS is credible in short-run and long-run relationship between employed variables favours the Post IFRS adoption on entrepreneurial entry, while discouraging entrepreneurial exit. Thus, there are correlations between the variables to predict the future trend on entrepreneurship entry in the long-run and short-run. In conclusion, it can be notices that with the non-current asset, current asset, total asset performed well, most especially the profit after tax in the mean descriptive statistics on post IFRS adoption. It is therefore recommended that quoted enterprise should put in place a system that would allow the enterprise prto epare its detailed annual financial statements to boost sustainability in the entrepreneurship entry. This will enables the reduction of entrepreneurship existing on enterprise winding up and closure by practicing IFRS adoptions in macro and micro enterprises.